Global distribution of tritium in JET with the ITER-like wall. (March 2021) - Lee, S.E.; Hatano, Y.; Tokitani, M.; Masuzaki, S.; Oya, Y.; Otsuka, T.; Ashikawa, N.; Torikai, Y.; Asakura, N.; Nakamura, H.; Isobe, K.; Kurotaki, H.; et al.
Highlights: Tritium (T) distributions in Be, W and W-coated CFC tiles from JET were examined. The center of Be outer limiter showed the highest T retention in the main chamber. The co-deposits in the divertor with high C fraction showed high T content. The C fraction and T content after 3rd campaign were low compared to 1st campaign. T retention in the bulk W tile was far smaller than that in the W-coated CFC tiles. Abstract: Nondestructive analysis of tritium (T) distribution was performed by means of imaging plate technique on specimens cut from the Be limiters, W-coated carbon tiles and bulk W lamellae retrieved from the JET tokamak after the first and third experimental campaigns with the ITER-like wall. Afterwards, analyses were continued using X-ray photoelectron spectroscopy, microscopy techniques and thermal desorption spectroscopy. Co-deposits formed on the W-coated tiles in the 1st campaign showed large T retention because of high carbon content reaching up to 50 atomic %, while the carbon fraction in co-deposits after the 3rd campaign was distinctly lower. The T retention of the plasma-facing surface of the bulk W tile was smaller than that of the W-coated tiles by a factor of 20, while deposition of small amount of T was found at the side surfaces facing to the gaps in a lamella structure. The correlation of T distributions with surface morphology and the discharge conditions is discussed.